2022
DOI: 10.1111/jonm.13828
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐methods systematic review of interventions to improve leadership competencies of managers supervising nurses

Abstract: Aim This study aimed to synthesize evidence on interventions to improve leadership competencies of managers supervising nurses. Background In recent years, numerous interventions have been developed to improve the leadership competencies of managers supervising nurses. However, researchers and nursing leaders are unclear about what aspects of interventions are effective for developing which competencies. Methods We conducted a mixed‐methods systematic review following the Joanna Briggs Institute (JBI) approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 115 publications
1
7
0
Order By: Relevance
“…The qualitative interviews of the present study brought to light the tangible usefulness of the Strengths-Based Nursing and Healthcare Leadership values to frame and structure an open, collaborative, and inclusive work environment. While Chen et al (2022) recent review concluded that many nurse leaders face difficulties applying the leadership competencies they acquire through intervention and training, we argue that this is not the case for Strengths-Based Nursing and Healthcare leaders. The Strengths-Based Nursing and Healthcare Leadership values are person-centred rather than performance-centred, an aspect that deeply resonated with the participating nurses and healthcare leaders.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The qualitative interviews of the present study brought to light the tangible usefulness of the Strengths-Based Nursing and Healthcare Leadership values to frame and structure an open, collaborative, and inclusive work environment. While Chen et al (2022) recent review concluded that many nurse leaders face difficulties applying the leadership competencies they acquire through intervention and training, we argue that this is not the case for Strengths-Based Nursing and Healthcare leaders. The Strengths-Based Nursing and Healthcare Leadership values are person-centred rather than performance-centred, an aspect that deeply resonated with the participating nurses and healthcare leaders.…”
Section: Discussionmentioning
confidence: 58%
“…Several leadership interventions for nurse leaders have been developed in the past 20 years. Two recent reviews of existing leadership interventions have been published ( Chen et al, 2022 ; Cummings et al, 2021 ), and both have shown generally positive outcomes of the interventions. Chen et al (2022) further highlighted that most programs were delivered in-person or through group work and that, in recent years, intervention programs have often incorporated more than one element in combination with in-person lectures or seminars, such as coaching and mentoring.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because toxic leaders assert upward influence tactics to conceal their incompetence (Milosevic et al , 2020), leadership development interventions to enrich their leadership competence can be seen as a potential strategy for handling toxic behavior in the workplace. In two separate systematic reviews (Chen et al , 2022; Cummings et al , 2021), interventions for leadership development, while seen to improve leadership behavior and practices in nurse managers, could also potentially reduce toxic and other undesirable behavior in nurse managers. Other leadership strategies may include leadership mentoring and coaching (Kanninen et al , 2021), leadership simulation (Labrague, 2021a, 2021b), leadership fellowship (MacPhee et al , 2012) and leadership certifications (Foster et al , 2018).…”
Section: Discussionmentioning
confidence: 99%